Swing kinematics described in Division I female softball players - Reilly-Boccia, C.; Ficklin, T.; Lund, R. (The Sport Journal, 2015)
The purpose of this study was to describe basic kinematic variables of the swing and the relationships that exist between these variables in Division I female softball players. These variables included bat velocity (BV), bat quickness (BQ), and bat acceleration (BA). Video data were collected for all swings during a 15-game softball tournament in which six NCAA Division I teams played. High-speed video cameras recording at 300 Hz were located along the first and third base lines recording every pitch. Data from 1,099 swings were analyzed for bat velocity (BV), bat quickness (BQ), and bat acceleration (BA). BQ and BV were calculated by video analysis and digitization. All swings were rank ordered by BA and assessed for relationships among BV, BQ, and BA. Descriptive statistics (mean ± SD) were calculated for all swing kinematic variables. Pearson product moment correlations were used to examine relationships among the swing kinematic variables. Alpha was set at (p<0.05) for all tests. Mean BV for all swings was 28.77 ± 4.94 m/s, mean BQ for all swings was 0.208 ± 0.042 s, and mean BA for all swings was 144.39 ± 38.44 m/s2. When observing correlations of all swings, BV and BQ unexpectedly had an inverse relationship. When grouping swings into homogenous strata based on BA, BQ, and BV proved to have a significant positive correlation.